A STUDY ON THE CORRELATION BETWEEN EMOTIONAL QUOTIENT (EQ) AND SPEAKING ACHIEVEMENT OF THE EIGHT YEAR STUDENTS'OF MTS NEGERI PLUPUH - AZIZAH, ELA NUR (2011)
This research paper is aimed at knowing whether or not there is correlation between Emotional Quotient (EQ) and speaking achievement of the eight year students of MTs Negeri Plupuh. Some of the students of eight year of MTs Negeri Plupuh find difficulties in facing the speaking test. They say that sometimes they feel unconfident and anxious in front of the teacher. Emotional quotient is a competence that includes self-controlling, spirit, diligence, and the competence of self-motivating. A competence to manage the negative emotion becomes the positive emotion. There are five aspects of emotional quotient: related to self emotion, managing self emotion, related to other‟s emotion or empathy, self-motivation, and making a relation. The subject of the research is the Eight year students of MTs Negeri Plupuh. There are 231 students who are divided into 5 classes. In collecting data, she gives the questionnaire, uses psychology test to the subject and uses the document to get speaking score from the mid semester score. The construct validity is used to know the validity of items by using correlation product moment, then to know the reliability she uses Alpha Cronbach. The correlation product moment is used to analyze the data. Based on the data calculation, it shows that the obtained of rxy is 0,474 when rtable is 0,297 at level of significance 0,05. If the obtained rxy is bigger than rtable, the obtained rxy is significant. So, there is significant correlation between Emotional Quotient (EQ) and speaking achievement. It means that the Emotional Quotient has a role in improving the speaking achievement; the students who have a high EQ will also have a good speaking achievement. The implication of this research for the English teacher of Mts Negeri plupuh is the possibility of changing the technique of teaching learning process of speaking in the classroom.